A 3‐Month Analysis of Disability, Quality of Life, and Disease Course in Patients With Migraine. Issue 2 (24th October 2012) - Raggi, Alberto; Leonardi, Matilde; Bussone, Gennaro; D'Amico, Domenico
Abstract : Objective: To describe a short‐term "real‐life" longitudinal evolution of migraine course, quality of life, and disability in a sample of patients attending to a specialty center and to evaluate the association between the changes in patient‐reported outcomes, number of reported headaches, their severity, and treatment consumption. Background: Clinical trials demonstrated that symptomatic and preventive therapies reduce migraine headache frequency and severity, thus improving quality of life and reducing disability. However, the longitudinal trajectory of health outcomes of patients under specific treatments but out of the setting of a clinical trial is almost unexplored. Design: Longitudinal observational study with a 3‐month follow‐up. Methods: Adult patients suffering from migraine, both with and without aura, were consecutively enrolled and administered the Migraine Disability Assessment, World Health Organization Disability Assessment Schedule, second version, and the Medical Outcome Survey 36‐Item Short‐Form Health Survey. Analysis of variance for repeated measures was used to assess longitudinal differences between baseline and the 3‐month follow‐up at employed assessments, number of days with headache in the previous 3 months and average judgment on attacks' severity, number of triptans and anti‐inflammatory drugs consumed for acute treatment of attacks; effect size was used to determine magnitude of change. Baseline differences between completers and non‐completers was evaluated with the independent‐sample t ‐test. Pearson's correlation was used to cross‐sectionally assess the association between total number of headache in the previous 6 months, average headache severity, total number of triptans and anti‐inflammatory drugs taken, and the scores observed at follow‐up for the 3 assessment instruments. The independent‐sample t ‐test was used to assess cross‐sectional differences between subjects taking preventive therapy and those taking only acute ones for total number of headaches, their severity, and total number of triptans and anti‐inflammatory taken, considering scores referred to the 3‐month follow‐up evaluation. Results: One hundred and two patients were enrolled (85.3% females; mean age 43.5) and 85 patients (85.9% females; mean age 44.3) completed the 3‐month follow‐up; no relevant differences between completers and non‐completers were observed. Small changes (effect size <0.50) were observed in longitudinal analysis, in particular for World Health Organization Disability Assessment Schedule scales, while frequency and severity of headaches were substantially stable. Few significant correlations were observed, in particular between the total number of days with headache and Migraine Disability Assessment score (0.54; P  < .01), and between the total number of days with headache and the total number of triptans taken (0.46; P  < .01). Compared with patients taking acute medication only, those on preventive therapy reported worse general health (mean 50.3, standard deviation [SD] 21.0 compared with mean 63.8, SD 16.5; t  = 3.31, P  = .001) and consumed less anti‐inflammatory drugs (mean 3.5, SD 5.6 compared with mean 7.5, SD 9.1; t  = 2.25, P  = .014). Conclusions: In this study, migraine frequency and intensity were almost stable over 3 months, and an evident trend toward improvement was found in disability and in some health‐related quality of life aspects, particularly in the social activity domain. Our results clearly indicate that continuity of care has a positive impact on patients' health status and functioning, also in stable patients already on anti‐migraine therapy, and that the use of patient‐oriented outcome measures is a viable way to capture such improvements.